2018
DOI: 10.1016/j.physleta.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Twinning to slip transition in ultrathin BCC Fe nanowires

Abstract: We report twinning to slip transition with decreasing size and increasing temperature in ultrathin <100> BCC Fe nanowires. Molecular dynamics simulations have been performed on different nanowire size in the range 0.404-3.634 nm at temperatures ranging from 10 to 900 K. The results indicate that slip mode dominates at low sizes and high temperatures, while deformation twinning is promoted at high sizes and low temperatures. The temperature, at which the nanowires show twinning to slip transition, increases wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…34 It is reported that nanowire orientation, size, temperature and strain rate could affect the deformation mechanism of the metal nanowire. 34,35,49 Herein, according to the features, the deformation mechanisms of Ni-Fe alloy nanowires vary with the Ni concentration. The Ni-Fe alloy nanowires with a low Ni concentration (0.5 and 5.0 at%) deform mainly by twinning mechanism under tensile loading.…”
Section: The Inuence Of the Ni Concentration On The Plastic Deformation Mechanism Of Fe-ni Alloy Nwsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 It is reported that nanowire orientation, size, temperature and strain rate could affect the deformation mechanism of the metal nanowire. 34,35,49 Herein, according to the features, the deformation mechanisms of Ni-Fe alloy nanowires vary with the Ni concentration. The Ni-Fe alloy nanowires with a low Ni concentration (0.5 and 5.0 at%) deform mainly by twinning mechanism under tensile loading.…”
Section: The Inuence Of the Ni Concentration On The Plastic Deformation Mechanism Of Fe-ni Alloy Nwsmentioning
confidence: 99%
“…The result is consistent with Choudhary's report that ultrathin <100> BCC Fe NWs deform by the dislocation slip mechanism at high temperatures while twinning dominates at low temperatures. 35 The dependence of the deformation mechanism on the Ni content and temperature could be attributed to the stacking fault energy.…”
Section: The Inuence Of the Ni Concentration On The Plastic Deformation Mechanism Of Fe-ni Alloy Nwsmentioning
confidence: 99%
See 1 more Smart Citation